Pemetaan Sebaran Salinitas di Desa Tanjung Pakis Kabupaten Karawang Menggunakan QGIS - Suhada, Bayu Aji Wicaksono; Adzillah, Wilma Nurrul; Purwanto, Aries (Universitas Batanghari Jambi, 2024)
The coastal area has a high likelihood of seawater intrusion, leading to the formation of brackish water. Brackish water is unsafe for consumption due to its high salt content, which exceeds 0.5 ppt. The purpose of this study is to identify the distribution of salinity by testing the well water of the residents in Tanjung Pakis Village, Karawang Regency. The sample determination method used is Systematic Grid Sampling. The grid used measures 1,000 x 250 m. In this study, 3 grids were used, each at different distances from the nearest coastline. Three samples were taken from each grid, resulting in a total of 9 samples. The parameter tested is salinity, which represents the salt content in the water. The method used to measure the salinity parameter is direct reading using a refractometer. The results of the study show that the highest salinity parameter value reached 120 ppt in Grid I, while the lowest salinity parameter value was 30 ppt in Grid II. The mapping results indicate high salinity values in Grid I, represented by a darker color. In Grid II, the salinity value decreases, indicated by a lighter color. An increase in salinity occurs in Grid III, shown by a darker color compared to Grid II.